The impact of integrating a good level of service into an inflexible sytem - González Pinzón, César Leonardo; Ñeco Caberta, Raúl; Ponce Corral, Carlos; Rodarte Dávila, Jesús (Visión electrónica, 2014)
At present, the level of service in manufacturing industries has brought about more commitments to satisfy customers with faster deliveries and a larger variety of product quality aspects. For this reason, industries need their material processing systems to respond effectively and self-adapt to market needs. In turn, this may generate high expenses when trying to offer a good level of service in a non-flexible manufacturing system. This investigation will show the case of a Colombian industry with little flexibility and an ease factor analysis fij , according to a variety of products that could be processed by the production line in a fast way.